Interventions in internal medicine wards with scope of clinical pharmacy residency program: A retrospective study - AYHAN, YUNUS EMRE; SANCAR, MESUT (My University, 2023)
Objective: Drug-related problems are a common health problem in hospitalized patients, affecting optimal patient outcomes. The aim of the study is to classify the drug-related problems detected by clinical pharmacy resident in hospitalized patients during their rotations and evaluate their interventions to the healthcare team. Material and Method: This is a retrospective study in which the drug-related problems of the patients hospitalized in the internal medicine wards between April and November 2018 were examined during the rotations of the clinical pharmacy resident. Patients’ demographics, prescribed medicine, laboratory findings were recorded. Drug-related problems are classified with the Pharmaceutical Care Network Europe Version 9.1 system. Result and Discussion: Ninety-two patients were included in the study. The median age of patients was 60.5 years and 59.8% of them were female. Most of the patients (63%) had three or more comorbidities. The most frequent comorbidities were hypertension (21.70%) and diabetes mellitus (10.64%). One hundred forty-seven drug-related problems were detected in 57 patients (62%). Potential drug-drug interactions (55.78%), errors in dosing timing instructions (9.52%), and inappropriate drug use according to guidelines (8.16%) were the most common causes of drug-related problems. The acceptance rate of interventions for resolving drug-related problems was 65%. The most common drug-related problems in this study were due to drug selection. The acceptance rate of recommendations for drug-related problems was lower than in the literature. However, this initial acceptance rate can be considered successful in a center where clinical pharmacy services have not been established.

Amaç: İlaçla ilgili sorunlar, hastanede yatan hastalarda optimal hasta sonuçlarını etkileyen yaygın bir sağlık sorunudur. Çalışmanın amacı, klinik eczacılık asistanının rotasyonları sırasında hastanede yatan hastalarda tespit ettiği ilaçla ilgili sorunları sınıflandırmak ve sağlık ekibine yapılan girişimleri değerlendirmektir. Gereç ve Yöntem: Bu çalışma, Nisan-Kasım 2018 tarihleri arasında iç hastalıkları servislerinde yatan hastaların klinik eczacılık asistanının rotasyonları sürecinde ilaçla ilgili sorunlarının incelendiği retrospektif bir çalışmadır. Hastaların demografik bilgileri, reçete edilen ilaçlar, laboratuvar bulguları kaydedildi. İlaçla ilgili sorunlar, Avrupa Farmasötik Bakım Ağı Versiyon 9.1 sistemi ile sınıflandırıldı. Sonuç ve Tartışma: Çalışmaya 92 hasta dahil edilmiştir. Hastaların ortanca yaşı 60.5’tir ve %59.8'i kadındı. Hastaların çoğunda (%63) üç veya daha fazla ek eşlik eden hastalık vardır. En sık eşlik eden hastalıklar hipertansiyon (%21.70) ve diabetes mellitus'tur (%10.64). Hastaların 57’sinde (%62) 147 adet ilaçla ilgili sorun saptandı. Potansiyel ilaç-ilaç etkileşimleri (%55.78), doz zamanlama talimatlarındaki hatalar (%9.52) ve kılavuzlara göre uygunsuz ilaç kullanımı (%8.16) ilaçla ilgili sorunların en yaygın nedenleri olarak belirlenmiştir. İlaçla ilgili sorunların çözümüne yönelik önerilerin kabul oranı %65'tir. Bu çalışmada en yaygın karşılaşılan ilaçla ilgili sorunlar ilaç seçiminden kaynaklanmaktadır. İlaçla ilgili sorunlar için önerilerin kabul oranı literatüre kıyasla daha düşüktür. Ancak klinik eczacılık hizmetinin henüz kurulmadığı bir merkezde bu ilk kabul oranları başarılı olarak kabul edilebilir
Klinik eczacılık uzmanlık programı kapsamında iç hastalıkları servislerindeki müdahaleler: Retrospektif bir çalışma
Keywords: Tıp; Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; TROPİKAL TIP; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; TROPICAL MEDICINE; PHARMACOLOGY & PHARMACY; Farmakoloji; Farmasötik bilim; Pharmacology; Pharmaceutical Science; Clinical pharmacy; drug-related; internal medicine; İç hastalıkları; ilaçla ilgili; klinik eczacılık; Clinical pharmacy; drug-related; internal medicine